Prehospital care in Malaysia: issues and challenges - Chew, Keng Sheng; Chan, Hiang Chuan (2011)
Prehospital care is defined as the phase of patient care from the point of injury or illness to the place of definitive treatment. As such, it is imperative that the patient is transported to the right place of care within the right time frame via the right mode of transportation by the right personnel. In this article, the authors explore seven components that are essential in the initial stage of any prehospital care system development-the components of manpower, training, communication, transportation, facilities, access to care and coordinated patient record keeping. The authors then address issues and challenges in these seven components within the Malaysian context. Because of geopolitical and logistic differences from one locality with another, it is not possible for a 'one-size-fit-all' solution to these issues and challenges within Malaysia. Ultimately, any effort to develop the prehospital care system should not be a mere stop gap measure, rather, it should address fundamental root problems in order to ensure sustainability and continuity of effort.